Innovative “Three-in-One” Method for Intervention of Lower Limb Neuropathic Pain: Retrospective Case Series Study - Lai J; Lai Y; Wu Y; Xiang Y; Zhang F (Local and Regional Anesthesia)
Jinyu Lai,1 Yan Lai,2 Yijun Wu,3 Yong Xiang,1 Fengqin Zhang1 1Department of Pain, Taihe Hospital, Hubei University of Medicine, Hubei, People’s Republic of China; 2Department of Ultrasound, Baihe County People’s Hospital, Shanxi, People’s Republic of China; 3Department of Radiology, Taihe Hospital, Hubei University of Medicine, Hubei, People’s Republic of ChinaCorrespondence: Yong Xiang, Department of Pain, Taihe Hospital, Hubei University of Medicine, Hubei, 442000, People’s Republic of China, Tel +86 719 13972451941, Email 411734468@qq.com Yijun Wu, Department of Radiology, Taihe Hospital, Hubei University of Medicine, Hubei, 442000, People’s Republic of China, Tel +86 719 13677198927, Email 82478224@qq.comPurpose: Minimally invasive intervention therapy anterior cutaneous branch of the femoral nerve for refractory neuropathic pain in the inner thigh area typically requires punctures at multiple sites to target the three nerves of the obturator nerve cutaneous branch, anterior cutaneous branch of the femoral nerve, and infrapatellar branch of the saphenous nerve. Clinical practice has demonstrated that the innovative “three-in-one” technique allows for simultaneous targeting of the three cutaneous nerves from a single entry point, effectively treating inner thigh pain. Moreover, this approach can also be used for local anaesthesia in shallow surgical procedures in the inner thigh area. We hope to promote this puncture technique among pain physicians.Patients and Methods: Clinical data of 8 patients with localized pain in the inner thigh from the Pain Department of Taihe Hospital, Shiyan City, Hubei Medical College, from April 2023 to September 2024 were collected. All the patients experienced pain in the cutaneous branch of the obturator nerve, the anterior branch of medial femoral cutaneous nerve, and the infrapatellar branch of the saphenous nerve. The “three-in-one” approach was used for nerve block and radiofrequency puncture.Results: After the “three-in-one” approach, the 8 patients showed varying degrees of improvement in their Numeric Rating Scale (NRS) scores. The patients were satisfied with the treatment method and efficacy, and no complications, such as nerve damage, occurred during the operation.Conclusion: The “three-in-one” approach is a potentially effective method for treating pain in the inner lower limb area, significantly reducing the damage caused by multiple puncture and providing ideas for more minimally invasive treatment of other areas; this approach meets expectations for more minimally invasive treatment.Plain language summary: With the continuous development of society and the increasing demand of patients for more comfortable treatment experience, minimally invasive puncture technology has become a direction pursued by more and more pain specialists. Our proposed “three-in-one” puncture technique is suitable for patients with lower limb medial pain. There is only one puncture point on the skin, and by adjusting the puncture direction, the surgeon can simultaneously block three nerves (the cutaneous branch of the obturator nerve, the anterior branch of medial femoral cutaneous nerve, and the infrapatellar branch of the saphenous nerve). This technology can also be used for pain treatment or auxiliary anesthesia in the inner thigh area. We also hope that our innovation can promote the development of more minimally invasive puncture technologies.Keywords: neuropathic pain, minimally invasive surgery, puncture technique, nerve block